Improving pregnancy outcomes in tertiary care institution in India through obstetric intensive care unit: three-year analysis - Gokhale, Ashish V.; Agarwal, Shonali; Modi, Dimpi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To analyse the requirement of high dependency unit (HDU)/intensive care unit (ICU) in an obstetric population in terms of utilization rate, indications for admission, interventions required and gestational outcome. Methods: Retrospective observational study was carried out from April 2015 to September 2018 at department of obstetrics and gynecology SSG Hospital, Vadodara India. Data related to indications for ICU admission, interventions required, length of stay and outcomes were collected, and results were analyzed. Results: Obstetric ICU utilization rate was 130 per 1000 deliveries. The major obstetric indications for admission were hypertensive disorders of pregnancy (42%) followed by anemia (25%) and post-partum hemorrhage (3%). In the rest of the patient’s majority (50%) had cardiovascular problems. Maternal mortality among these critically ill women was 3.76%. The death rate in the present study was high among patients admitted for non-obstetric (74.54%) as opposed to obstetric indications (25.46%). Conclusions: Establishment of well managed high dependency and intensive care unit in health care facilities dealing with high volumes of high-risk maternity cases reduces the maternal mortality significantly and results in improved maternal outcomes.